2018
DOI: 10.4067/s0716-10182018000400377
|View full text |Cite
|
Sign up to set email alerts
|

Factores relacionados a candidiasis oral en niños y adolescentes con VIH, caracterización de especies y susceptibilidad antifúngica

Abstract: Factors related to oral candidiasis in HIV children and adolescents, species characterization and antifungal susceptibility Background: Factors associated with candidiasis and colonization in HIV-positive children and adolescents in developing countries are not well understood. Aim: To identify the factors associated with oral Candida colonization and candidiasis in institutionalized HIV-positive children and adolescents in Tijuana, México, as well as the response of the isolates to antifungals. Materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
6
1
2
Order By: Relevance
“…31 Some researchers reported that oral Candida colonization significantly correlated with the increase in viral load and the decrease in the number of CD4 cells. 24,28 De Brito Costa et al 32 found that oral C. albicans colonization correlated with a decrease in CD4 cell count in their study of HIV-positive children. In the present study, Candida colonization was not detected in oral samples of five HIV-positive children with CD4 count of 200 cells/mm 3 but was found in 65 of those with CD4 count >200 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 Some researchers reported that oral Candida colonization significantly correlated with the increase in viral load and the decrease in the number of CD4 cells. 24,28 De Brito Costa et al 32 found that oral C. albicans colonization correlated with a decrease in CD4 cell count in their study of HIV-positive children. In the present study, Candida colonization was not detected in oral samples of five HIV-positive children with CD4 count of 200 cells/mm 3 but was found in 65 of those with CD4 count >200 cells/mm 3 .…”
Section: Discussionmentioning
confidence: 97%
“…Most commonly isolated NAC species were reported as Candida guilliermondii (23.1%), Candida tropicalis (15.4%), and Candida lusitaniae (7.3%) by Cerqueira et al 3 ; C. krusei (11.4%) and C. parapsilosis (7.14%) by Alves et al 20 ; C. guilliermondii (23%), C. tropicalis (17%), and C. lusitaniae (8%) by Pomarico et al 15 ; Candida glabrata (33%), C. kefyr (13%), C. lipolytica (7%), and C. tropicalis (7%) by Castillo-Martínez et al 24 In the present study, unlike other studies, these Candida species were not isolated from oral samples of HIV-infected patients. It was found that all the cultured strains were rare species, including C. dubliniensis (18.2%), Candida famata , Candida zeylanoides , and Candida colliculosa (4.5% each).…”
Section: Discussionmentioning
confidence: 99%
“…The asymptomatic phase is marked by being asymptomatic or presenting an adenoid syndrome with the presence of firm, but not woody, mobile, non-painful lymph nodes without changes in the overlying skin, occupying two or more adjacent regions [ 20 , 21 ]. During the AIDS phase, immunosuppression is exacerbated with a considerable loss of CD4 lymphocytes and significant viral replication, neoplasms, and opportunistic infection [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Hivmentioning
confidence: 99%
“…Las especies del género Cándida forman parte del microbiota normal en la piel, cavidad oral, tracto digestivo y vagina. Diferentes especies se han descrito como patógenos oportunistas involucrados en infecciones superficiales y sistémicas, especialmente en pacientes con inmunosupresión así se tiene a Candida albicans (Torres Ramos et al, 2006), Candida krusei, Candida tropicalis, Candida glabatra Candida dunliniensis, Candida parapsilosis, Candida lusitaniae, Candida guilliermondi y Candida spp (Cruz Quintana et al, 2017;Llanos González et al, 2017;Torrealba Camacho et al, 2016), siendo la candidiasis la micosis oral más frecuente en el ser humano (Bengel, 2010;Castillo-Martinez et al, 2020;Ibañez Mancera et al, 2017;Lazo et al, 2018;Mariel-Carballo, 2019); además es posible encontrar, Histoplasma capsulatum (Prieto & Calvo, 2004),…”
Section: Hongosunclassified
“…Sin embrago en el presente estudio se trabajó con el aislamiento de hongos de importancia clínica aisladas a partir de las diversas mascarillas utilizadas por los pobladores de los distritos de Campoverde, Manantay, Callería y Yarinacocha. (Cruz Quintana et al, 2017;Llanos González et al, 2017;Torrealba Camacho et al, 2016), siendo la candidiasis la micosis oral más frecuente en el ser humano (Bengel, 2010;Castillo-Martinez et al, 2020;Ibañez Mancera et al, 2017;Lazo et al, 2018;Mariel-Carballo, 2019).…”
Section: Otra De Las Familias Bacterianas Encontradas Fue Micrococcac...unclassified